Impact of Bad Air Quality on the Morphology of Lungs - A Radiological Cross-Sectional Study Conducted at a Tertiary Care Hospital in Lahore. - Haider, Syed Nayab; Iqbal, Muhammad Wasif (Journal of University College of Medicine and Dentistry, 2022)
Objective: To radiologically examine the impact of bad air quality on the x-ray findings of patients visiting a tertiary care hospital in Lahore. Material and Methods: This cross-sectional study was conducted in the outpatient department of CPTH, Lahore, from 1st of Oct. to 1st of Dec. 2021. A total of 40 patients from age groups between 21 – 60 years and from both genders, who presented with respiratory symptoms, were included in the study for their x-ray findings. As this was a radiological study, there was only one clinical parameter taken into consideration and that was x-ray chest. The patients enrolled in the study were divided into 4 groups, based on the severity of symptoms and findings on x-rays. Only non-smokers were included in the study. Results: Out of 40 patients, 18 showed no changes on x-ray chest, 12 showed minor appearance of unilateral peri bronchiolar shadows, 6 showed a more prominent appearance of peribronchiolar shadows bilaterally whereas 4 showed bilateral signs of lung fibrosis. Conclusion: Exposure to smog filled air can be linked to accelerated development of lung damage, even among people who have never smoked.